A Privacy-Preserving System for Targeted Coupon Service - Jing Yao; Yifeng Zheng; Yu Guo; Chengjun Cai; Anxin Zhou; Cong Wang; Xiaolin Gui (IEEE Access, 2019)
It is increasingly popular to use behavioral targeting in online coupon service for targeted coupon delivery, wherein customized coupons can be delivered to only eligible users whose behavioral profiles match targeting profiles specified by the vendor. While allowing the vendor to personalize the service and build loyalty, such practice also raises the security challenges of protecting users' behavioral profiles and the vendor' targeting profiles. Our research caters for the trend of targeted coupons yet aims to offer privacy assurance. Unlike prior works which are largely constrained by the mere support for secure behavioral targeting, we ambitiously target a new system design that uniquely provides comprehensive functionalities to satisfy practical needs. Specifically, we explore and present the first full-fledged system design for targeted coupon service with three practical functionalities: (i) Private range search on coupon discounts: it enables a user to securely search for encrypted targeted coupons with certain discount range; (ii) Private behavioral targeting: it ensures that only eligible users can decrypt the ciphertexts of targeted coupons obtained from search; (iii) Private blockchain-empowered coupon redemption: it enables coupon redemption to be securely and transparently settled on the blockchain. We conduct extensive experiments and the results show that our secure system design is practically affordable.